(untitled) (Pedagogy of Higher and Secondary Education, 2008)
This article is devoted to the peculiarities of theory and technologies of contextual teaching, possibilities of their introduction into the process of training and upbringing in a higher educational establishment of MIA of Ukraine. Also some experience of teaching Ukrainian and foreign languages for future law enforcers according to the contextual model of teaching is given; it helps to improve the quality of their training and upbringing.